Emotion Beliefs and Emotion Regulation Strategies Associated With Anxiety Symptoms Among Grade 7–8 Adolescent Students in China - Qin Zhang; Chenyang Shang; Xiaohua Li; Yajie Huang; Lixia Cui (SAGE Open)
The current study aimed to investigate the relationship among two fundamental emotional beliefs (controllability and goodness), emotion regulation strategies, and anxiety symptoms. The study evaluated the mediatory effects of emotion regulation strategies on the relationship between emotion beliefs and anxiety. Grade 7 and 8 adolescents in China ( n  = 598) answered relevant questionnaires. Results demonstrated that individuals who believed that emotions were relatively controllable or that anxiety was relatively good reported lower levels of anxiety. Further, the link between beliefs about emotion controllability and anxiety was partially mediated by reappraisal and rumination, suggesting that believing that emotions were relatively controllable could reduce anxiety via increased reappraisal and less rumination. Decreased rumination was more important in early adolescents. Additionally, the link between beliefs about anxiety goodness and anxiety symptoms was also mediated by reappraisal, suggesting that adolescents who believed that anxiety was relatively good were more likely to adopt reappraisal, which in turn decreased anxiety symptoms. These findings contribute to our understanding of emotion beliefs of early adolescents in China and their effects. They suggest that enhancing controllable beliefs about emotion and good beliefs about anxiety in adolescents who are less likely to actively regulate their emotions may be valuable in reducing their anxiety.